Immigration in the Spanish nation - Mengibar, Ana Caballero (Tensões Mundiais, 2018)
The literature suggests that Spain has never had a national identity but is rather an amalgam of regional identities. The accession to the European Union and the arrival of immigrants present new challenges to Spanish identity. Forging a national identity entails both building a solidarity based on ‘belongingness’ and excluding certain groups that might constitute a threat. These contemporary forms of exclusion aligned with immigration can be referred to as neo-racist.